PEMANFAATAN SERBUK ECENG GONDOK UNTUK MENURUNKAN KADAR KADMIUM (Cd) PADA AIR SUMUR GALI MASYARAKAT DI DESA NAMO BINTANG KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG TAHUN 2012 - Sri Lestari .; Devi Nuraini Santi; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Society in Desa Namo Bintang using water wells that contains high levels of Cd that exceeded the quality standard due to groundwater contamination from landfill waste, so that it was required a method to reduce levels of Cd in water wells in the village. This study aimed to know determine levels of Cd in water wells and to utilize the hyacinth powder for reducing levels of Cd in water wells. The type of this research was Quasi Experiment with the Completely Randomized Design as study design. Object of this research was the water wells with higher levels of Cd was more than 0,005 mg/L, the treatment was by adding10 mg, 20 mg and 30 mg hyacinth powder with three repetitions in an effort to reduce the levels of Cd in water wells. The results showed that the initial levels of Cd in water wells was0,00685 mg/L, the levels of Cd in water wells which did not receive additional of hyacinth powder (as control) did not show any reduction, meanwhile by adding 10 mg, 20 mg and 30 mg hyacinth powder respectively reduce for 28,8%, 33,72%, 26,28%. The test results of Two Way Anova showed there were significant differences in the treatment of various Cd levels decrease (p=0,000< 0,005). The test result of Bonferroni indicated that the addition of 20 mg hyacinth powder was the most effective between the others for reducing the levels of Cd in water wells in the village. Therefore for the people in the Namo Bintang village expected to utilize the hyacinth powder to reduce levels of Cd so that the water that used become more clean and accordance with standards estabilished. Keywords: Water Wells, Hyacinth Powder, Cd Levels